Could neutrophil to lymphocyte ratio be a marker in Hashimoto's thyroiditis? - Onalan, Erhan; Aslan, Mehmet (Pakistan Medical Assoc, 2020)
Objective: To determine the applicability of neutrophil/lymphocyte ratio as diagnostic and prognostic marker in patients with Hashimoto's thyroiditis. Methods:The retrospective cross-sectional study was conducted at Elazig Firat University, Elazig, Turkey, and comprised data of Hashimato's thyroiditis patients aged 18 years or more admitted between January 1, 2017, and November 1, 2018. A healthy control group was also included to work as controls. Thyroid-stimulating hormone, free triiodothyronine, free thyroxine, anti-thyroid peroxidase, complete blood count, and C-reactive protein results were obtained from patient files for both the cases and the controls, and neutrophil/lymphocyte ratio was computed NLR for both the groups. Data was analysed using SPSS 22. Results: Of the 477 subjects, 377(79%) were cases with a mean age of 45.3 +/- 13.8 years, and 100(21%) were controls with a mean age of 36.6 +/- 10.7 (p<0.001). Neutrophil/lymphocyte ratio was statistically higher in the cases compared to the controls (p< 0,05). Neutrophil/lymphocyte ratio had a negative correlation with thyroid-stimulating hormone, free thyroxine and anti-thyroid peroxidise but it was non-significant (p>0.05). Conclusion: Neutrophil/lymphocyte ratio was found to be an effective low-cost marker in the diagnosis and follow-up of Hashimato's thyroiditis.
Keywords: Hashimoto's thyroiditis; Neutrophil/lymphocyte ratio; Chronic inflammation